2020
DOI: 10.1007/s10571-020-00991-3
|View full text |Cite
|
Sign up to set email alerts
|

If Artificial In Vitro Microenvironment Can Influence Tumor Drug Resistance Network via Modulation of lncRNA Expression?—Comparative Analysis of Glioblastoma-Derived Cell Culture Models and Initial Tumors In Vivo

Abstract: The tumor resistance of glioblastoma cells in vivo is thought to be enhanced by their heterogeneity and plasticity, which are extremely difficult to curb in vitro. The external microenvironment shapes the molecular profile of tumor culture models, thus influencing potential therapy response. Our study examines the expression profile of selected lncRNAs involved in tumor resistance network in three different glioblastoma-derived models commonly utilized for testing drug response in vitro. Differential expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…An article was illustrated AC064875.2 as potential prognostic biomarker may regulate neutrophil in ltration in glioma [39]. MIR210HG was reported up-regulation upon hypoxia exposure in glioma cells, and was considered a resistance in GBM therapy [40,41]. Transcriptome sequencing and qRT-PCR con rmed that lncRNA SMIM25 was high expression in cerebral cavernous malformations on the before study [42].…”
Section: Discussionmentioning
confidence: 99%
“…An article was illustrated AC064875.2 as potential prognostic biomarker may regulate neutrophil in ltration in glioma [39]. MIR210HG was reported up-regulation upon hypoxia exposure in glioma cells, and was considered a resistance in GBM therapy [40,41]. Transcriptome sequencing and qRT-PCR con rmed that lncRNA SMIM25 was high expression in cerebral cavernous malformations on the before study [42].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA AC064875.2 shows potential prognostic biomarker and may regulate neutrophil infiltration in glioma ( 42 ). Similarly, MIR210HG was reported up-regulation upon hypoxia exposure in glioma cells, and was considered a resistance in GBM therapy ( 43 , 44 ). Transcriptome sequencing and qRT-PCR confirmed that lncRNA SMIM25 had high expression in cerebral cavernous malformations ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the results of the analysis of EMT markers in cell lines derived from tumors of various types indicate that the levels of TYMS mRNA are increased in cell lines with a predominance of the mesenchymal-like phenotype (Siddiqui et al 2017 ). However, some caution should be exercised when comparing the results of lncRNA interaction in cell lines in vitro with respect to the interaction of the complex network of non-coding RNA in metastatic cancer cells (Witusik-Perkowska et al 2022 ).…”
Section: Malat1 and Other Lncrnas Affecting The Level Of Ty...mentioning
confidence: 99%